Bioactivity flavonoids from roots of Euphorbia tirucalli L. (February 2021) - de Lima, Maria de Fátima Rocha; Cavalcante, Luziene A.; Costa, Emily Cintia Tossi de Araújo; de Veras, Bruno Oliveira; da Silva, Márcia Vanusa; Cavalcanti, Lívia Nunes; Araújo, Renata Mendonça
Graphical abstract: Highlights: Two flavonoids and one ellagic acid derivative were isolated from the roots of Euphorbia tirucalli . 13 compounds were identified by HPLC-MS/MS analysis. Ethanol extract from roots of E. tirucalli and the isolated compounds displayed significant antimicrobial activity. Abstract: Euphorbia tirucalli (Euphorbiaceae) is a species widely utilized for popular medicine in northeast of Brazil because of its innumerable reported medicinal properties. The HPLC-Qtrap-MS/MS analysis from E. tirucalli roots ethanol extract revealed that this species presents 8 flavonoids and 5 shikimate derivative compounds. Chemical studies of these ethanolic extract using chromatographic procedures allowed the isolation of four previously unreported compounds for this species: myricetin, 3, 3'-dimethoxy-4- O -α-rhamnopyranoside-ellagic acid, 4- O -methyl-gallic acid and ampelopsin. All structures were determined using 1D and 2D NMR spectroscopy analysis. The ethanol extract and four isolated compounds were evaluated for antimicrobial activity against Staphylococcus aureus, Escherichia coli, Sporothrix brasiliensis and Candida albicans . All the analyzed compounds presented activity against all evaluated bacteria and fungi, with MIC values ranging from 8 to 2048 μg/mL.